Primary angiitis of the central nervous system - Gianno, Francesca; Antonelli, Manila; d’Amati, Antonio; Broggi, Giuseppe; Guerriero, Angela; Erbetta, Alessandra; Caputi, Luigi; Marucci, Gianluca (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2024)
Primary angiitis of the central nervous system (CNS) is an uncommon inflammatory disorder, with highly variable clinical presentation. It needs to be differentiated from several mimickers, such as CNS involvement in systemic vasculitides, connective tissue disorders, infectious disease, and leukodystrophy as well as neoplastic diseases. The diagnosis requires a combination of clinical and laboratory investigations, multimodal imaging, and histopathological examination, which should be available for confirmation. In the present paper, the histopathological features of primary angiitis of the CNS are described and highlighted to help pathologists avoid misdiagnosis of a treatable acquired disease.